G-сходимость параболических операторов и слабая сходимость решений диффузионных уравнений - Махно, С.Я. (Український математичний журнал, 1993)
The upper estimates and, in some special cases, the lower estimates of the rate of rational approximation of piecewise-analytic functions defined on touching continuums are established. The upper and the lower estimates are consistent and depend on the mutual location of these continuums.